2001
DOI: 10.1002/1098-2795(200103)58:3<262::aid-mrd3>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of nitric oxide for murine oocyte maturation, embryo development, and trophoblast outgrowth in vitro

Abstract: We investigated the extent to which NO participates in the developmental competence (oocyte maturation, fertilization and embryo development to blastocyst) using an in vitro culture system adding sodium nitroprusside (SNP), NO donor, and NOS inhibitor (N‐omega‐nitro‐L‐arginine methyl ester, L‐NAME). We also assessed the effects of NO/NOS system on blastocyst implantation using an in vitro trophoblast outgrowth assay. The treatment of low concentrations of SNP (10−7 M) significantly stimulated meiotic maturatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(89 citation statements)
references
References 38 publications
6
81
0
2
Order By: Relevance
“…The stage specific defects induced by NO depletion underscores the influence of the tissue micro-environment on NO-mediated actions during vascular development. These differences in susceptibility may be the result of developmental stage specific sensitivity to environmental conditions (Barroso et al, 1998;Sengoku et al, 2001). The observed sensitivity of primitive streak conceptuses to changes in NO concentration is currently unexplained; we speculate that differentiation and migratory events that occur in the splanchnic mesoderm specifically at this stage may be affected, while in late head fold stage embryos these events have been completed.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The stage specific defects induced by NO depletion underscores the influence of the tissue micro-environment on NO-mediated actions during vascular development. These differences in susceptibility may be the result of developmental stage specific sensitivity to environmental conditions (Barroso et al, 1998;Sengoku et al, 2001). The observed sensitivity of primitive streak conceptuses to changes in NO concentration is currently unexplained; we speculate that differentiation and migratory events that occur in the splanchnic mesoderm specifically at this stage may be affected, while in late head fold stage embryos these events have been completed.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that high concentrations of NO donor (0.1 and 1 mM DETA/NO) in vivo impaired embryo development while lower concentrations (1 and 10 µM) did not cause developmental abnormalities (Barroso et al, 1998;Sengoku et al, 2001). Therefore, we supplemented low doses of a slow, steady release NO donor (NOC-18) to the culture media and assessed the tolerance of the yolk sac to exogenous NO (20 µM) during vasculogenesis.…”
Section: Exogenous No Treatment Results In Normal Vascular Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…NO is now thought to represent a vital component of the oocyte microenvironment as it plays a physiological role during oocyte maturation, fertilization, and beginning of embryo development (Jablonka-Shariff & Olson 1998, Sengoku et al 2001, Bergandi et al 2014.…”
Section: No In Oocyte Competencementioning
confidence: 99%